Cross-linked anion exchange membranes with flexible, long-chain, bis-imidazolium cation cross-linker. (26th October 2021) - Xu, Fei; Qiu, Ke; Li, Jing; Lin, Bencai; Ding, Jianning
Abstract: Herein, poly (phenylene) oxide (PPO)-based cross-linked anion exchange membranes (AEMs) with flexible, long-chain, bis-imidazolium cation cross-linkers are designed and synthesized. Although the cross-linked membranes possess high ion exchange capacity (IEC) values of up to 3.51–3.94 meq g −1, they have a low swelling degree and good mechanical strength because of their cross-linked structure. Though the membranes with the longest flexible bis-imidazolium cation cross-linker (BMImH-PPO) possess the lowest IEC among these PPO-based AEMs, they show the highest conductivity (24.10 mS cm −1  at 20 °C) and highest power density (325.7 mW cm −2  at 60 °C) because of the wide hydrophilic/hydrophobic microphase separation in the membranes that promote the construction of ion transport channels, as confirmed by atom force microscope (AFM) images and the small angle X-ray scattering (SAXS) analyses. Furthermore, the BMImH-PPO samples exhibit good chemical stability (10% and 6% decrease in IEC and conductivity, respectively, in 2 M KOH at 80 °C for 480 h, and a 22% decrease in weight in Fenton's reagent at 60 °C for 120 h), making such cross-linked AEMs potentially applicable in alkaline anion exchange membrane fuel cells. Highlights: PPO-based cross-linked AEMs with flexible, long-chain, bis-imidazolium cation cross-linkers were synthesized. Obvious hydrophilic/hydrophobic microphase separation and excellent chemical stability of AEMs were highlighted. The AEMs with high IEC show a low swelling degree and good mechanical strength.